World book 2001. Vol. 20 U-V / Mary Alice Anderson - Anderson, Mary Alice (Estados Unidos de América: World book, Inc, 2001)
Ukraine, facts in brief, government, people, way of life, the land, climate, economy, history, important dates in Ukraine, additional resources, unemployment in the united states, in Canada, wheat unesco does, how unesco is organized, history, way of life, soviet influence in eastern Europe, question, United Kingdom, government, population density, people, way of life, the land, climate, economy, important dates in Britain, the general assembly.
Portada ilustrada, mapa, cuadro
Col. Enc
Keywords: 1. ENCICLOPEDIA 2. WORLD BOOK U-V VOL.20 3. REFERENCIA